Architected fibrous scaffolds for engineering anisotropic tissues. (27th July 2021) - Reid, James Alexander; Dwyer, Kiera D; Schmitt, Phillip R; Soepriatna, Arvin H; Coulombe, Kareen LK; Callanan, Anthony
Abstract: Mimicking the native three-dimensional microenvironment is of crucial importance when biofabricating a new healthcare material. One aspect of the native tissue that is often omitted when designing a suitable scaffold is its anisotropy. Not only is matching native mechanical properties important when designing implantable scaffolds or healthcare materials, but matching physiological structure is also important as many cell populations respond differently to fiber orientation. Therefore, novel aligned electrospun scaffolds with varying fiber angles and spacing of bundles were created and mechanically characterized. Through controlling the angle between the fibers in each layer of the scaffold, a range of different physiological anisotropic mechanical properties were achieved that encompasses values found in native tissues. Extrapolation of this mechanical data allowed for any native tissue's anisotropic Young's modulus to be mimicked by electrospinning fibers at a particular angle. These electrospun scaffolds were then incorporated with cell-laden hydrogels to create hybrid structures that contain the benefits of both scaffolding techniques with the ability to encapsulate cells in the hydrogel. To conclude, this study develops a novel bundled fiber scaffold that was architected to yield anisotropic properties matching native tissues.